Usability Evaluation of the SanguPalu E-Government Mobile Application Using PSSUQ and UMUX: a Case Study in Palu - Mohammad Hikmal Naki; Deny Wiria Nugraha (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2026)
The SanguPalu mobile application is a e-government digital service platform developed by the Palu City Government to enhance accessibility, transparency, and efficiency in public service delivery. Despite its comprehensive features, user feedback indicates issues related to interface clarity, navigation efficiency, and system consistency, suggesting potential usability problems. This study aims to evaluate the usability level of the SanguPalu application using a descriptive quantitative approach integrating the Post-Study System Usability Questionnaire and the Usability Metric for User Experience. Data were collected from 118 active users through an online survey. Usability was assessed using average scores of PSSUQ subscales and a global UMUX score. The results show that system usefulness achieved a score of 2.87 (upper limit), while information quality obtained a score of 2.87 (lower limit). Interface quality recorded the highest score of 3.09 (above upper limit), indicating the most critical usability issue. The overall PSSUQ score was 2.93 (upper limit). The UMUX analysis produced a score of 65.20, reflecting a marginal-to-high usability level consistent with the PSSUQ findings. By combining subscale-specific and global usability measurements, this study offers a more nuanced understanding of usability issues in a local government mobile application context. These findings indicate that while SanguPalu adequately supports core service functions, improvements in interface design and navigation structure are essential to strengthen user satisfaction and overall service quality.